2019
DOI: 10.1108/jsm-01-2018-0046
|View full text |Cite
|
Sign up to set email alerts
|

Factors for and against resistance to smart services: role of consumer lifestyle and ecosystem related variables

Abstract: Purpose Consumers are increasingly connected to, and make use of, a multitude of technologies in their daily lives. The exponential growth in the use of Internet of Things (IoT)-based services is ushering in a new era of e-services, in which the service experience is becoming autonomous (intelligence), devices are intercommunicating (connectivity) and consumers can access the service anytime, anywhere and using any device (ubiquity). However, a number of challenges have arisen. The purpose of this paper is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 63 publications
5
99
0
1
Order By: Relevance
“…This result is consistent with previous studies in wearable technology adoption which reported complexity perception as a barrier in adoption (e.g. Chouk & Mani, 2019 ; Ko, Sung, & Yun, 2009 ).…”
Section: Data Integration and Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is consistent with previous studies in wearable technology adoption which reported complexity perception as a barrier in adoption (e.g. Chouk & Mani, 2019 ; Ko, Sung, & Yun, 2009 ).…”
Section: Data Integration and Discussionsupporting
confidence: 93%
“…Previous studies in wearable devices mostly consider the complexity of working with the device in general and were not specific to each phase (e.g. Chouk & Mani, 2019 ; Ko et al, 2009 ). As our survey and interview results show, users are more concerned about the second phase, which is reading the output.…”
Section: Data Integration and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead this research is not supported by Paskaleva & Cooper (2017), highlighting disappointment with the role and contribution of the community and other actors in the life cycle of production (management and evaluation of public services) smart city. Chouk & Mani (2019), showed that consumer lifestyle factors reduce consumer resistance to smart services.…”
Section: Conclusion:-mentioning
confidence: 99%
“…A study by Siugzdiniene et al, (2017), states that public governance systems cannot be considered as intelligent social systems, where some intelligence characteristics have been well expressed, but smart public governance is not yet part of the culture of the Lithuanian city government. Chouk & Mani (2019), showed that consumer lifestyle factors reduce consumer resistance to smart cities.…”
mentioning
confidence: 99%